Illegal street vending on Bulawayo central business district urban space: challenges and possible solutions - Simango, Lawrence (Midlands State University, 2017)
People are forced into street vending due to various factors. First and foremost street vending is a source of livelihood for the urban poor and those who couldn’t be absorbed into the formal sectors of the economy. Zimbabwe is facing a plethora of economic challenges and under such a precarious state of affairs street vending activities are on the rise. The astronomical growth of street entrepreneurs is an addition to multifarious challenges faced by urban local authorities in most developing countries globally. Despite efforts made by urban regulatory authorities through the provision of vending bays in designated areas to cater for the informal sector, illegal street vendors continues to invade the central business district of most cities in total violation of cities By-Laws. Such disregard of the local laws has forced civic authorities to take stern measures to curb the invasion of the CBD by the illegal street vendors. On the other end such measures are seen as a total disregard of human rights and the turbulent economic environment by the groups that advocate for the interests of street vendors. Street vending, is the most visible sub-sector of informal economy and is a common feature of cities in Zimbabwe in general and Bulawayo in particular. This study sought to unearth the motivations, character and context for street vending using an empirical study of the experience in Bulawayo, the second largest of Zimbabwe and industrial hub of the country. Results of the study shows that there are a plethora of challenges caused by illegal street vending in the central business district of Bulawayo. On the other end street vendors themselves are also faced with multiple challenges when conducting their businesses. The study therefore, seeks to explore all the possible solutions and policy options that can be considered for adoption by the Bulawayo City Council in order to handle the phenomenon. The study used the mixed method research approach. Mixed research is a synthesis that includes ideas from qualitative and quantitative research. Data was collected mainly through the administration of 80 questionnaires to illegal street vendors operating in the CBD of Bulawayo and in-depth interviews with the Bulawayo City Council managers, Bulawayo Progressive Residents Association, Bulawayo Vendors and Traders Association and Officials from the Zimbabwe Republic Police. The observation technique was also used to study the activities and behaviour of street vendors. The study used stratified, convenience and purposive sampling techniques. Results show that measures taken by the civic authorities to curb illegal street vending have been largely unsuccessful. Lack of employment has been cited as the major driver of illegal street vending activities. The study recommends that the regulatory authorities should learn constructive lessons from successful participatory models from Durban Municipality in South Africa through projects like the Warwick Junction Urban Renewal Project.